The diva takes the cake - Davis, Krista (Davis, Krista. Domestic diva mystery, 2009)
Sophie's sister Hannah is getting married. But when the groom's ex-wife is found hanging from a tree, the Domestic Diva fears her sister is about to wed a killer.